2019
DOI: 10.1186/s12199-019-0822-8
|View full text |Cite
|
Sign up to set email alerts
|

Medical empirical research on forest bathing (Shinrin-yoku): a systematic review

Abstract: Aims: This study focused on the newest evidence of the relationship between forest environmental exposure and human health and assessed the health efficacy of forest bathing on the human body as well as the methodological quality of a single study, aiming to provide scientific guidance for interdisciplinary integration of forestry and medicine. Method: Through PubMed, Embase, and Cochrane Library, 210 papers from January 1, 2015, to April 1, 2019, were retrieved, and the final 28 papers meeting the inclusion c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
145
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(160 citation statements)
references
References 58 publications
12
145
1
2
Order By: Relevance
“…CIM exercises offers a range of preventive possibilities that may also include MBM approaches (91,92,(107)(108)(109). Exercise practiced in open air such as Nordicwalking or a walk in the forest may have greater overall positive effects than fitness training in a studio or indoor home situations (110,111).…”
Section: Exercisementioning
confidence: 99%
“…CIM exercises offers a range of preventive possibilities that may also include MBM approaches (91,92,(107)(108)(109). Exercise practiced in open air such as Nordicwalking or a walk in the forest may have greater overall positive effects than fitness training in a studio or indoor home situations (110,111).…”
Section: Exercisementioning
confidence: 99%
“…In recent years researchers have begun to explore the possibility that outdoor recreational activity experiences may have therapeutic benefit to military veterans with PTSD. Outdoor recreational experiences have attracted a multitude of labels including 'green exercise' [23,28], 'therapeutic recreation' [29], 'forest bathing' [30] 'peer outdoor support therapy' [31], 'nature adventure rehabilitation' [32], 'nature based therapy' [33] and 'nature recreation experience' [34]. These interventions often combine the benefits of a natural environment with learning a new recreational skill from certified professionals.…”
Section: An Alternative Approach: Outdoor Recreation Experiencesmentioning
confidence: 99%
“…A study conducted in Japan found forest bathing activities were effective at lowering blood pressure and improving negative emotions in working-age adults [37]. Five systematic reviews evaluated the effects of forest bathing on health and well-being [17,18,20,38,39]. One review of 28 studies assessed the effects of forest bathing and concluded that forest bathing was effective at reducing levels of depression in adults [18].…”
Section: Introductionmentioning
confidence: 99%
“…Three other reviews-one of six randomized controlled trials and another two of 68 studies and 28 studies-examined the multiple physiological and psychological benefits of spending time in a forest [20,38,39]. These three reviews reported that forest therapy had beneficial effects on blood pressure, heart rate, pulse rate, and immune function, led to a reduction in inflammation, a decrease in the secretion of stress hormones, an improvement in cardiopulmonary functions and endocrine function, and to a reduction in depression and improvement in mood [20,38,39]. However, these reviews concluded that evidence of the therapeutic effects of forest bathing was insufficient to establish clinical guidelines on its use as a health promotion or disease prevention strategy for preventive medicine.…”
Section: Introductionmentioning
confidence: 99%